Social network sites as a means to support personal social capital and well-being in older age: An association study - Marianne Simons (Elsevier, 2021)
This study aims to gain a better understanding of the potential benefits of social network sites (SNS) as a means to help support personal social capital and well-being of older adults. Results are reported of a cross-sectional study in which a sample of Dutch older adults (n ​= ​410) with a social network site account and varying in age from 50 to 93 (M=64.6, SD ​= ​8.2) filled out a questionnaire including validated scales measuring SNS use, personal bonding and bridging social capital and psychological, social and emotional well-being. Regression analyses including relevant covariates supported our hypotheses that; (1) SNS use is positively associated with personal bonding social capital; (2) SNS use is positively associated with personal bridging social capital; (3) SNS use is positively associated with psychological well-being and (4) SNS use is positively associated with social well-being. No significant association was found between SNS use and emotional well-being. Although no conclusions of causality can be drawn, these results support the assumed potential of SNS as a means to help preserve personal social capital and well-being at an older age and add to the, still limited, research literature on this topic. Theoretical and practical implications of these findings are discussed.